2018
DOI: 10.1167/iovs.18-24428
|View full text |Cite
|
Sign up to set email alerts
|

The Corneal Basement Membranes and Stromal Fibrosis

Abstract: PurposeThe purpose of this review was to provide detailed insights into the pathophysiology of myofibroblast-mediated fibrosis (scarring or late haze) after corneal injury, surgery, or infection.MethodLiterature review.ResultsThe epithelium and epithelial basement membrane (EBM) and/or endothelium and Descemet's basement membrane (BM) are commonly disrupted after corneal injuries, surgeries, and infections. Regeneration of these critical regulatory structures relies on the coordinated production of BM componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 74 publications
2
73
0
7
Order By: Relevance
“…B), thus indicating that EVs travel further than just to adjacent cells within the cornea; however, it is unknown whether the EVs are moving to a site or simply moving at random. Finally, EVs are unable to penetrate the corneal basement membrane, which agrees with multiple publications that once the basement membrane is reformed and barrier function restored, topical applications of therapeutics are unable to affect the stroma (Medeiros et al, ); however, in this study, EVs appear to penetrate Descemet's membrane (Fig. C,D).…”
Section: Discussionsupporting
confidence: 86%
“…B), thus indicating that EVs travel further than just to adjacent cells within the cornea; however, it is unknown whether the EVs are moving to a site or simply moving at random. Finally, EVs are unable to penetrate the corneal basement membrane, which agrees with multiple publications that once the basement membrane is reformed and barrier function restored, topical applications of therapeutics are unable to affect the stroma (Medeiros et al, ); however, in this study, EVs appear to penetrate Descemet's membrane (Fig. C,D).…”
Section: Discussionsupporting
confidence: 86%
“…However, when EBM regeneration is impaired (such as in corneal scarring, alkali burn, and PKP), TGF-b and PDGF penetrate the stroma at high levels, leading to myofibroblast development and maturation, finally causing corneal scarring or fibrosis. 53,55,56 In this study, we found that activated corneal resident fibroblasts and invading fibrocytes, both having been reported to develop into myofibroblasts, 44 underwent senescence after epithelial debridement. These senescent cells expressed vimentin and a-SMA, but a few cells expressed desmin, characteristic of a fully developed myofibroblast.…”
Section: Discussionmentioning
confidence: 52%
“…78,84 Normal versus defective BM regeneration likely relates to the type and severity of the stromal injury and results from inadequate production or incorrect localization of BM components-including laminins, nidogens, perlecan, and collagen type IV. 82,91 Corneal epithelial injury triggers release of IL-1 and apoptosis of the underlying keratocytes mediated by Fas-Fas ligand system in a manner that is proportional to the size of the original injury. 92 Extensive loss of keratocytes delays BM regeneration because of a deficiency or inadequate localization of some BM components contributed by keratocytes to the EBM.…”
Section: Fibrocytes In Corneal Wound Healing and Fibrosismentioning
confidence: 99%